2023
DOI: 10.21037/jtd-23-1371
|View full text |Cite
|
Sign up to set email alerts
|

Association between cigarette smoking history, metabolic phenotypes, and EGFR mutation status in patients with non-small cell lung cancer

Xiaohui Zhang,
Xiuyu Guo,
Qiaoling Gao
et al.

Abstract: Background Cigarette smoking exerts a significant impact on metabolic phenotypes and epidermal growth factor receptor ( EGFR ) mutation status; however, their correlation remains insufficiently established. Therefore, the aim of this study was to investigate the association between cigarette smoking history, metabolic phenotypes, and EGFR mutation status in patients with non-small cell lung cancer (NSCLC). Methods We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Zhang et al found that compared with NSCLC patients who smoked, non-smoking patients were more sensitive to EGFR tyrosine kinase inhibitors and had better prognosis. In addition, it was found that non-smoking patients had a higher maximum standardized uptake value of primary tumors and a lower incidence of EGFR mutations ( 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…Zhang et al found that compared with NSCLC patients who smoked, non-smoking patients were more sensitive to EGFR tyrosine kinase inhibitors and had better prognosis. In addition, it was found that non-smoking patients had a higher maximum standardized uptake value of primary tumors and a lower incidence of EGFR mutations ( 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…Smoking is identified as another significant risk factor for lung cancer (70,71). Prolonged cigarette consumption is known to contribute to airway remodeling and is implicated in the etiology of lung cancer and various pulmonary diseases (72).…”
Section: Discussionmentioning
confidence: 99%